2013
DOI: 10.1097/shk.0b013e318276f4ca
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Bacterial and Mitochondrial DNA Distinguish Bacterial Sepsis From Sterile Systemic Inflammatory Response Syndrome and Quantify Inflammatory Tissue Injury in Nonhuman Primates

Abstract: Systemic inflammatory response syndrome (SIRS) is a fundamental host response common to bacterial infection and sterile tissue injury. SIRS can cause organ dysfunction and death but its mechanisms are incompletely understood. Moreover, SIRS can progress to organ failure or death despite being sterile or after control of the inciting infection. Biomarkers discriminating between sepsis, sterile SIRS and post-infective SIRS would therefore help direct care. Circulating mitochondrial DNA (mtDNA) is a damage-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 36 publications
1
63
0
2
Order By: Relevance
“…These mediators activate neutrophils in circulation promoting non-specific organ attack and suppressing chemotactic responses to infective stimuli [29]. Recent evidence further suggests that in response to stimuli such as trauma [32] and microbial infection [33] cellular mtDNA levels decrease while circulating cell-free mtDNA levels are increased [34]. To that effect, Nakahira et al showed that mtDNA could serve as a viable plasma biomarker in medical ICU patients and that increased circulating mtDNA was associated with mortality [35].…”
Section: Discussionmentioning
confidence: 99%
“…These mediators activate neutrophils in circulation promoting non-specific organ attack and suppressing chemotactic responses to infective stimuli [29]. Recent evidence further suggests that in response to stimuli such as trauma [32] and microbial infection [33] cellular mtDNA levels decrease while circulating cell-free mtDNA levels are increased [34]. To that effect, Nakahira et al showed that mtDNA could serve as a viable plasma biomarker in medical ICU patients and that increased circulating mtDNA was associated with mortality [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the elevation of ATP in BALF is observed in patients with IPF (129) or asthma (65), the elevated levels of ATP are also observed in BALF from the experimental mice models of fibrosis (129) or bronchial hypersensitivity (65). Similarly, the levels of circulating cell-free mtDNA are elevated in patients with trauma (167,179) or sepsis (82,167) and also observed in animal models of trauma/hemorrhagic shock (178) or bacterial sepsis (155). In addition, the exogenous administration of mitochondrial DAMPs is able to develop the similar pathological conditions with human diseases in animals.…”
Section: The Mitochondrial Damps In Human Diseasesmentioning
confidence: 99%
“…DAMPs, damage-associated molecular patterns; FPR, formyl peptide receptor; TLR, toll-like receptor. To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars (155). Serum: Acetaminophen-induced acute liver injury in mice (97).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent experimental data, however, suggest that a prolonged SIRS may be more a reflection of host immune activity than an indication of the presence of viable microorganisms. [13][14][15] As such, efforts have begun to shorten the duration of antimicrobial therapy in the presence of traditional markers of sepsis. These efforts have already been successful in other severe infections such as ventilator-associated pneumonia.…”
Section: Discussionmentioning
confidence: 99%